Postbuckling Analysis of Functionally Graded Beams Using Hyperbolic Shear Deformation Theory - Bouazza, Mokhtar; Amara, Khaled; Zidour, Mohamed; Tounsi, Abedlouahed; Adda-Bedia, EL Abbas (Review of Information Engineering and Applications, 2015)
In the present study, post-buckling of a thick FGM rectangular beam is carried out using the hyperbolic shear deformation theory (HYSDT). The theory accounts for parabolic distribution of transverse shear stresses across the thickness satisfying the stress free boundary conditions at top and bottom surfaces of the beam. It is assumed that elasticity modulus is changing in the thickness direction and all other material properties are taken to be constant. Variation of elasticity modulus in the thickness direction, are described by a simple power law distribution in terms of the volume fractions of constituents. Governing equations of FGM beam for post-buckling problem were found by applying Hamilton principle and Navier type solution method was used to solve post-buckling problem. The results obtained for post-buckling analysis of functionally graded beams are compared with those obtained by other theories, to validate the accuracy of the presented theory.